1998
DOI: 10.1023/a:1024442802113
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder and family functioning in adolescent cancer

Abstract: Twenty three adolescents with a history of cancer, 27 physically abused adolescents, and 23 healthy, nonabused adolescents were administered structured posttraumatic stress disorder (PTSD) interviews and self-report questionnaires regarding family functioning. Thirty five percent of adolescent cancer subjects met criteria for lifetime PTSD as compared to only 7% of the abused adolescents: 17% of the cancer subjects and 11% of the abuse subjects met criteria for current PTSD. Adolescents with cancer viewed thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
4
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(131 citation statements)
references
References 29 publications
4
122
4
1
Order By: Relevance
“…Inspection of our data, however, did not demonstrate extreme high levels of adaptability and cohesion in the families under study. Previous studies showed inconsistent results on this point [46,[59][60][61][62].…”
Section: Discussionmentioning
confidence: 83%
“…Inspection of our data, however, did not demonstrate extreme high levels of adaptability and cohesion in the families under study. Previous studies showed inconsistent results on this point [46,[59][60][61][62].…”
Section: Discussionmentioning
confidence: 83%
“…Posttraumatic Stress Disorder (PTSD) is an anxiety disorder that can occur after severe life trauma, including life-threatening illness. Field trials and studies that have examined the relationship between cancer survival and PTSD have found that a substantial number of survivors report symptoms consistent with PTSD (Alter et al, 1996;Stuber et al, 1996;Pelcovitz, 1998). Rates of PTSD appear to be lower in pediatric and adolescent cancer survivors (Butler et al, 1996;Erickson and Steiner, 2002;Kazak et al, 2004) than young adult samples, with about 20% of young adult childhood cancer survivors meeting PTSD criteria (Hobbie et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35][36][37][38] The reported ages of participating survivors ranged from 7 years 21 to 71 years. 29 With regard to the heterogeneity of diagnoses, the majority of studies examined survivors of all cancers, with seven studies excluding central nervous system malignancies, 17,19,22,25,31,34,38 and only one focusing on Hodgkin's lymphoma survivors.…”
Section: Study Methodologiesmentioning
confidence: 99%
“…29 With regard to the heterogeneity of diagnoses, the majority of studies examined survivors of all cancers, with seven studies excluding central nervous system malignancies, 17,19,22,25,31,34,38 and only one focusing on Hodgkin's lymphoma survivors. 29 The majority (number [n] =14) of studies examined both PTSS and PTSD outcomes; five assessed PTSD alone 16,18,25,36,37 and four evaluated PTSS alone. 22,27,34,38 Sample sizes ranged from 23-6,542, with ten samples of less than 100, 17,19,[23][24][25][30][31][32]36 eleven samples between 100 and 350, 18,20,22,26,29,[33][34][35]37,38 and two samples exceeding 6,500.…”
Section: Study Methodologiesmentioning
confidence: 99%